Biodistribution and organ oxidative damage following 28 days oral administration of nanosilver with/without coating in mice. Issue 6 (26th January 2020) - Gan, Junying; Sun, Jindu; Chang, Xiaoru; Li, Wenhua; Li, Jiangyan; Niu, Shuyan; Kong, Lu; Zhang, Ting; Wu, Tianshu; Tang, Meng; Xue, Yuying
Abstract: This study evaluated the biodistribution and organ oxidative effects of silver nanoparticles (AgNPs) coated with/without polyvinylpyrrolidone (PVP) (AgNP‐20 and AgNP‐PVP) in mice; these were administered by gavage at a dose of 10‐250 mg/kg body weight per day for 28 days. The results showed that both the AgNPs could induce subacute toxicity and oxidative damage to mice and were mainly accumulated in the liver and spleen and excreted by feces. AgNPs could be absorbed into blood and might cross the blood‐brain barrier, and be distributed extensively in mice. The malondialdehyde content in the liver, lungs and kidneys increased in both AgNP groups, while the content of glutathione decreased, and the activity of superoxide dismutase increased at first and then decreased along with the increased doses. Inflammatory pathological changes in the lung and liver at high dose of both AgNPs were consistent with increases in glutamate pyruvic transaminase, glutamate oxaloacetic transaminase and the total protein in serum detection. The Ag content was detected in organs, with the highest content in the liver, followed by spleen, while the Ag content in feces was about 500 times higher than that in urine. AgNP‐PVP could induce higher oxidative stress and subacute toxicity than AgNP‐20 at the same dose, which might be related to the higher concentrations and more Ag + ions released in mice after AgNP‐PVP exposure. The data from this research provided information on toxicity and biodistribution of AgNPs following gavage administration in mice, and might shed light for future application of AgNPs in daily life. Abstract : The biodistribution and organ oxidative effects of nanosilver with/without coating were evaluated by general behavior, body weight, organ coefficient, serum biochemistry, histopathology and Ag content detection following oral administration in mice for 28 days. It was found that the two Ag nanoparticles (NPs) could cause subacute toxicity and organ oxidative damage to mice, and were distributed extensively in the body of mice. The toxicity caused by 20 nm silver nanoparticles coated with polyvinylpyrrolidone (AgNPs‐PVP) was greater than that caused by silver nanoparticles without coating at 20 nm (AgNPs‐20).